EVALUASI KEBIJAKAN TAMBANG MINYAK DAN GAS BUMI (MIGAS) - Ridwan Ridwan; Lailul Mursyidah (Universitas Bina Taruna Gorontalo, 2023)
The purpose of this research is to find out how well oil and gas management policies comply with applicable regulations. The research location is in Jambe Bay, Kedungbanteng Village, Tanggulangin District, Sidoarjo Regency. Interviews, observations, and written notes were used as data collection methods in this qualitative research. As well as primary and secondary data are used as data sources. The research findings show that PT. MinarakBrantas Gas in managing the gas mine in TelukJambe, Kedungbanteng village, tends to ignore the applicable regulations as stipulated in Law No. 22 of 2001 concerning Oil and Gas and Regional Regulation No. 6 of 2009 concerning spatial planning for the Sidoarjo Regency area in 2009-2029. It can be seen as follows: (1) In terms of policy effectiveness, mining business actors have not been effective in providing employment opportunities for local communities and have not been effective in developing village territories (2) In terms of policy responsiveness, it can be seen from the rejection of the community which has an impact on gas mining activities (3) In terms of policy smoothing, with the existence of a mining licensing policy, mine managers will benefit more than the affected communities. (4) Regarding the accuracy of the policy, the management of the gas mine in the village of Kedungbanteng is dominated by negative impacts such as damaged roads and land subsidence which causes flooding in settlements and rice fields belonging to the people of Kedungbanteng village